Hubungan Partisipasi Orang Tua Dan Minat Belajar Dengan Hasil Belajar Siswa Kelas IV SDN Kampung Implementasi Perubahan (KIP) Maccini Kota Makassar - Latang Latang; Fatmawati Gaffar; Lirhan Lirhan; Muhamad Ihsan Azhim (Phinisi Integration Review, 2022)
This research examines the relationship between parental participation and student interest in learning with fourth grade students' learning outcomes at SDN KIP Maccini Makassar City. The main problem studied is how is the relationship between Parental Participation and Student Interest in Learning with the Learning Outcomes of Class IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Makassar City for the 2020/2021 academic year. The purpose of this study was to determine the relationship between parental participation and student learning interest with the learning outcomes of fourth graders at SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Makassar City for the 2020/2021 academic year. Type of research  used is a quantitative research with the type of correlational studies. The research sample used was saturated sampling, namely class IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini with a total of 43 students consisting of 17 male students and 26 female students. Data collection techniques used in this study were questionnaires, documentation and observation. Data was collected from the distribution of questionnaires to students and parents and then analyzed by Inferential Statistical Data Analysis. From the results of the study, there is a large relationship between Parental Participation and Student Interest in Learning with the Learning Outcomes of Class IV Students at SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Makassar City. The presence of parental participation shows that there is a significant relationship with increasing student interest in learning outcomes for fourth grade students at SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Makassar City. Penelitian ini menelaah Hubungan Partisipasi Orang Tua Dan Minat Belajar Siswa Dengan hasil Belajar Siswa Kelas IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Kota Makassar. Permasalahan pokok yang dikaji yaitu bagaimanakah Hubungan Partisipasi Orang Tua Dan Minat Belajar Siswa Dengan hasil Belajar Siswa Kelas IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Kota Makassar tahun ajaran 2020/2021. Tujuan penelitian ini yaitu untuk mengetahui Hubungan Partisipasi Orang Tua Dan Minat Belajar Siswa Dengan hasil Belajar Siswa Kelas IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Kota Makassar tahun ajaran 2020/2021. Jenis penelitian yang digunakan yaitu penelitian kuantitatif dengan desain correlational studies. Sampel penelitian yang digunakan adalah sampling jenuh,yaitu kelas IV SDN KIP Maccini dengan jumlah 43 siswa yang terdiri dari 17 orang siswa laki-laki dan 26 orang siswa perempuan. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu penyebaran angket,dokumentasi dan observasi. Data dikumpulkan dari penyebaran angket pada siswa dan orang tua kemudian dianalisis secara Analisis Data Statistik Inferensial. Dari hasil penelitian besar hubungannya Partisipasi Orang Tua Dan Minat Belajar Siswa Dengan hasil Belajar Siswa Kelas IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Kota Makassar. Adanya partisipasi orang tua menunjukkan bahwa besar hubungan yang signifikan terhadap Peningkatan Minat Belajar Siswa Dengan hasil Belajar Siswa Kelas IV SDN KAMPUNG IMPLEMENTASI PERUBAHAN (KIP) Maccini Kota Makassar.